Profit and principle : Hugo Grotius, natural rights theories and the rise of Dutch power in the East Indies, 1595-1615 - Van Ittersum, Martine Julia, 1968-; Grotius, Hugo, 1583-1645. (Leiden ; Boston : Brill, 2006)
This monograph is a study of the interaction of politics and political theory in The Netherlands and Asia in the early seventeenth century. Its focal point is the Dutch jurist Hugo Grotius (1583-1645), who developed his rights and contract theories for the benefit of the United Dutch East India Company or VOC. The monograph reconstructs the immediate historical context of his political thought, as conceptualized in his early manuscript De Jure Praedae/On the Law of Prize and Booty and Mare Liberum/The Free Sea (1609). It argues that Grotius' justification of Dutch interloping in the colonial empires of Spain and Portugal made possible the VOC's rise to power in the Malay Archipelago, which resulted in the slow, but steady, loss of selfdetermination on the part of the inhabitants of the Spice Islands.
Jacob van Heemskerck's capture of the Santa Catarina and its justification in De Jure Praedae (1604-1606) -- Hugo Grotius and the Spanish black legend: humanist historiography and moral philosophy in De Jure Praedae --Why was De Jure Praedae written? -- Hugo Grotius and the peace negotiations between Spain and the United Provinces, 1607-1608 -- Hugo Grotius and the truce negotiations between Spain and the United Provinces, 1608-1609 -- VOC spokesman and lobbyist during the Twelve Years' Truce.
Includes bibliographical references (pages 493-510) and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Nederlandsche Oost-Indische Compagnie -- History; Grotius, Hugo, -- 1583-1645.; East India Company -- History; Grotius, Hugo, -- 1583-1645; East India Company; Nederlandsche Oost-Indische Compagnie; Verenigde Oostindische Compagnie; Grotius, Hugo; Netherlands -- Commerce -- East Indies; East Indies -- Commerce -- Netherlands; Natural law; International law -- History -- 17th century; International relations; Imperialism; Pays-Bas -- Commerce -- Indes orientales; Indes orientales -- Commerce -- Pays-Bas.; Droit naturel; Droit international -- Histoire -- 17e siècle.; Relations internationales; Impérialisme.; international relations; LAW -- International; Commerce; Imperialism; International law; International relations; Natural law; Asia -- East Indies; Netherlands; Machtpolitik; Wirtschaftspolitik; Grundrecht; Natuurrecht; Politieke filosofie; Overzeese expansie; Vereenigde Oost-Indische Compagnie; 1600-1699; History